Efeito da temperatura de solubilização na microestrutura, dureza, início da transformação martensítica e textura de um aço maraging 300 - Barrio, Regina Coeli Araújo Vieira Gunyics (2019)
The understanding of the relationship between ultra high strength steels mechanical properties and microstructure remains a key problem in metallurgy with important consequences for the industry, notedly the high performance industry such as nuclear, petrochemical and aerospace. These applications require combination of high mechanical strength and good toughness, as well as good weldability, high corrosion resistance, etc. However, many hardening mechanisms result in a dilemma of the antagonism between mechanical strength and toughness, making it indispensable researches for a solution that optimizes the two properties, improving its performance and increasing the range of possibilities of its application. In this work, the effects of the solution annealing temperature on the microstructure, hardness, martensitic transformation and texture of the maraging 300 steels were evaluated. Seven solution annealing temperatures were evaluated for a time of one hour of treatment and three aging temperatures for three hours of treatment. The microstructural characterization was performed by optical microscopy to determine the grain size of the primary austenite and analysis of the microstructure, X-ray diffraction and diffraction of backscattered electrons. The results showed that the solution annealing temperature above the conventional one had little influence on the crystallographic texture of the material. It was also observed that there is a hardness peak at 1000 ° C and that there is a relationship between the grain size of the previous austenite and the martensite morphology. It is concluded that the grain size of the previous austenite also influences the beginning temperature of the martensitic transformation.